2016
DOI: 10.5935/0103-5053.20160038
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilicity Study of Thiazolo[3,2-a]pyrimidine Derivatives as Potential Bioactive Agents

Abstract: Systems containing fused thiazole and pyrimidine rings play a significant role in organisms due to their biological activity. Lipophilicity, as important parameter to expect biological activity of the compounds, was evaluated for 27 potentially active thiazolo[3,2-a]pyrimidine derivatives using chromatographic methods: reversed phase thin layer chromatography (RP-TLC) and reversed phase high performance liquid chromatography (RP-HPLC) methods. Methanol was used as the organic modifier of the mobile phases. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…The methylene group disposed at the second position of the thiazolidine fragment can be considered as one of the most attractive for functionalization because of its high activity in condensation reactions, especially when combined with either aromatic or heterocyclic aldehydes. It was shown that the products obtained by this method can exhibit a wide range of biological activity, i.e., they can act as antitumor agents [8,9] and act as effective growth inhibitors of the Bcl-2 protein that protects the tumor cells from many types of apoptosis [10,11], CDC25 phosphatase that plays a key role in the regulation of the cell reproduction cycle and is usually observed in many types of cancer, casein kinase, and protein kinase [12,13]. Some examples of inhibition of ISPF proteins of Mycobacterium tuberculosis, Plasmodium falciparum, and A. thaliana by such type of compounds were also reported [14].…”
Section: Introductionmentioning
confidence: 99%
“…The methylene group disposed at the second position of the thiazolidine fragment can be considered as one of the most attractive for functionalization because of its high activity in condensation reactions, especially when combined with either aromatic or heterocyclic aldehydes. It was shown that the products obtained by this method can exhibit a wide range of biological activity, i.e., they can act as antitumor agents [8,9] and act as effective growth inhibitors of the Bcl-2 protein that protects the tumor cells from many types of apoptosis [10,11], CDC25 phosphatase that plays a key role in the regulation of the cell reproduction cycle and is usually observed in many types of cancer, casein kinase, and protein kinase [12,13]. Some examples of inhibition of ISPF proteins of Mycobacterium tuberculosis, Plasmodium falciparum, and A. thaliana by such type of compounds were also reported [14].…”
Section: Introductionmentioning
confidence: 99%
“…The single crystal X-ray diffraction study revealed that the supramolecular motif in the crystalline phase of the obtained compounds can be controlled by adjusting the interplay between various types of noncovalent interactions such as H-, Br-π, O-π, π-π bonding through the rational choice of the substituents at C2, C5, and C6 atoms. Depending on the used 2-or 4-hydroxybenzylidene derivatives, the self-assembly pathway leads to the formation of racemic H-bonded dimers (11,12) or infinite 1D homochiral chains (13,14), respectively, which can be explained by the close disposition of H-bond donor and H-bond acceptor observed for 11 and 12, and relatively high H-accepting ability of N8 pyrimidine atom in the case of 13 and 14. Moreover, the 1D chains can be generated for 2-hydroxybenzylidene by involving protic EtOH or MeOH acting as bridges in intermolecular H-bonding between the obtained heterocycles (10-MeOH).…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that up to now no anti-tumor activity of the described compounds is studied. In addition, compound 1 has demonstrated high absorption ability in the gastrointestinal tract due to optimal hydrophilicity/lipophilicity of the molecule [11]. The related compound 2 (Figure 1) has been used for the growth of Bcl-2 proteins inhibitor which leads to many types of tumor cells apoptosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…8 Lipophilicity parameters were determined by chomatographic method, using RP-HPLC as follow. 17,18 Reversed-phase HPLC…”
Section: Methodsmentioning
confidence: 99%